Seasonal Variation and Sexual Dimorphism of the Microbiota in Wild Blue Sheep (Pseudois nayaur) - Zhu, Zhaoling; Sun, Yewen; Zhu, Feng; Liu, Zhensheng; Pan, Ruliang; Teng, Liwei; Guo, Songtao (Frontiers in Microbiology, 2020)
Microbiota of the wild blue sheep (Pseudois nayaur) presents a seasonal variation due to different dietary selection and feeding strategy from different ecological niches chosen by different sex in summer. To address those issues we analyzed the variation of gut microbiota based on the material from the feces, with 16s RNA and meta-genome aimed to explore seasonal and gender differences. The results indicate that seasonal dietary changes and gender differentiation, as expected, cause the variation in sheep’s gut microbiome structure，the variation by the former is more significant than the latter. Compared with winter group, summer group is featured by abundant enzymes digesting cellulose and generating short-chain fatty acids (SCFAs), such as beta-glucosidase (EC: 3.2.1.21) for cellulose digestion and butyrate kinase(EC:2.7.2.7) for butyrate metabolism, implying the changes of the components in intestinal flora allow the sheep to adapt to the seasonalized dietary selection through alternated digestive functions to reach the goal of facilitating the efficiency of energy harvesting. The results also show that the blue sheep expresses a prominent sexual dimorphism in the components of gut microbiota, indicating the two sexes have different adaptations to dietary selection, and demands for physical and psychological purposes. Thus, this study provides an ideal model of demonstrating the principles and regulations of natural selection, and environmental adaptation.selection, and demands for physical and psychological purposes.